Pengaruh Kepemimpinan Kepala Sekolah dan Supervisi Akademik Terhadap Profesionalisme Guru (Penelitian di MA Yapisa dan MA Ar-Raudloh) - Sinta Fitriyani; Uus Ruswandi; Badruddin Badruddin (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2022)
The purpose of this study is to determine the improvement of teacher professionalism to be achieved. So that good management activities are needed, including the leadership of the principal and academic supervision so that teachers are able to carry out their duties and functions with maximum ability in guiding students. The research approach used in this study is Mixed Methods Research, which is research that combines quantitative and qualitative methods with sequential explanatory models (sequence of proof). Quantitative and qualitative data collection using questionnaires, interviews, observations and documentation studies. The results of this study show that; 1) The principal's leadership obtained high qualifications, 2) Academic supervision obtained high qualifications, 3) Teacher professionalism obtained good qualifications, 4) There was a positive and significant influence of the principal's leadership on professionalism, 5) There was a positive and significant influence of academic supervision on teacher professionalism, 6) There was a positive and significant influence of principal leadership and academic supervision on teacher professionalism, 7) The principal's leadership quantitatively is no different from the principal's leadership qualitatively, 8) Academic supervision quantitatively is no different from academic supervision qualitatively, and 9) Teacher professionalism quantitatively is no different from teacher professionalism qualitatively in MA Yapisa and MA Ar-Raudloh.